Determinants influencing the performance of Fair trade coffee farmers in Tanzania - Pyk, Filippa (SLU/Dept. of Economics, 2018)
Abstract This study aimed to identify the major determinants of performance among Fair trade certified small-scale coffee growers in the Kagera region, northwest Tanzania. The analysis is based on survey data collected through field interviews with a sample of Tanzanian Fair trade certified farmers during the period March-April 2017. The standard regression model was used to find what affects annual revenue and productivity. The estimation results suggest that experience within farming and coffee plot size have a positive effect on annual coffee revenue. Likewise the farmers perceived importance of NGOs is estimated to have a positive impact on revenue. Perceived access to financial support however showed to have a negative impact on revenue. Further, experience within the farming business showed to have a negative impact on coffee productivity. Perceived access to financial support and extension service also showed to negatively affect productivity. The estimated result for determinants of productivity likely suffers from simultaneous bias and should be interpreted with caution.